Road Users in Rural Areas Mobility: Impact from Fuel Price - Zakaria, Husna; Md. Rohani, Munzilah (Recent Trends in Civil Engineering and Built Environment, 2023)
There has been a great deal of research that has shown that the mobility pattern of people is heavily influenced by their monthly incomes and wages. Fuel price increases have impacted the monthly budget of certain people, leading them to reduce their travel activities or change their modes of transport. Rural people have fewer options for transport modes than urban people, and most of them use their own vehicles for travel. Therefore, they may travel differently than urban people, especially if travel costs increase as a result of the rise in fuel prices. This study examines the changes in mobility patterns of rural people as a result of fuel price fluctuations. This study involved rural people living in Johor, Malaysia. The survey data were analyzed using Statistical Package for Social Science (SPSS) and Microsoft Excel software. SPSS is a statistical package for social science research. Based on the results of this study, the respondents (N = 205) did not change their daily travel patterns regardless of the rise in fuel prices (significance level, 0.05).